Modeling and Evaluating Denial of Service Attacks for Wireless and Mobile Applications - Lu, Zhou.; Wang, Wenye; Wang, Cliff; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This SpringerBrief covers modeling and analysis of Denial-of-Service attacks in emerging wireless and mobile applications. It uses an application-specific methodology to model and evaluate denial-of-service attacks. Three emerging applications are explored: multi-modal CSMA/CA networks, time-critical networks for the smart grid, and smart phone applications. The authors define a new performance metric to quantify the benefits of backoff misbehavior and show the impacts of a wide range of backoff mishandling nodes on the network performance, and propose a scheme to minimize the delay of time-critical message delivery under jamming attacks in smart grid applications. An investigation on the resilience of mobile services against malware attacks is included to advance understanding of network vulnerabilities associated with emerging wireless networks and offers instrumental guidance into the security design for future wireless and mobile applications. This book is appropriate for students, faculty, engineers, and experts in the technical area of wireless communication, mobile networks and cyber security.
Modeling and Evaluation of Backoff Misbehaving Nodes in CSMA/CA Networks -- Modeling the Impact of Jamming Attacks on Time-Critical Traffic with Applications to Smart Grid -- Minimizing Message Delay of Time-Critical Traffic for Wireless Smart Grid Applications under Jamming -- Understanding the Resilience of Mobile Cloud Services to Malware.
Keywords: Computer security; Computer Communication Networks; Systems and Data Security; Computer Communication Networks; Information Systems Applications (incl. Internet).